Use of high-plex data provides novel insights into the temporal artery processes of giant cell arteritis - Parreau, Simon; Molina, Elsa; Dumonteil, Stéphanie; Goulabchand, Radjiv; Naves, Thomas; Bois, Melanie C.; Akil, Hussein; Terro, Faraj; Fauchais, Anne-Laure; Liozon, Eric; Jauberteau, Marie-Odile; Weyand, Cornelia M.; et al. (Frontiers in Immunology, 2023)
Objective: To identify the key coding genes underlying the biomarkers and pathways associated with giant cell arteritis (GCA), we performed an in situ spatial profiling of molecules involved in the temporal arteries of GCA patients and controls. Furthermore, we performed pharmacogenomic network analysis to identify potential treatment targets. Methods: Using human formalin-fixed paraffin-embedded temporal artery biopsy samples (GCA, n = 9; controls, n = 7), we performed a whole transcriptome analysis using the NanoString GeoMx Digital Spatial Profiler. In total, 59 regions of interest were selected in the intima, media, adventitia, and perivascular adipose tissue (PVAT). Differentially expressed genes (DEGs) (fold-change > 2 or < −2, p-adjusted < 0.01) were compared across each layer to build a spatial and pharmacogenomic network and to explore the pathophysiological mechanisms of GCA. Results: Most of the transcriptome (12,076 genes) was upregulated in GCA arteries, compared to control arteries. Among the screened genes, 282, 227, 40, and 5 DEGs were identified in the intima, media, adventitia, and PVAT, respectively. Genes involved in the immune process and vascular remodeling were upregulated within GCA temporal arteries but differed across the arterial layers. The immune-related functions and vascular remodeling were limited to the intima and media. Conclusion: This study is the first to perform an in situ spatial profiling characterization of the molecules involved in GCA. The pharmacogenomic network analysis identified potential target genes for approved and novel immunotherapies.